IMPACT OF EARLY SUCCESSFUL PPCI ON LEFT VENTRICULAR EJECTION FRACTION AMONG STEMI CASES - KAMAL, S; KHAN, AS; EMMAN, UE; KHAN, SA; ADEEL, .; QAZI, K (Biological and Clinical Sciences Research Journal, 2024)
Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality worldwide, making holistic health management essential for patients. Psychological well-being, particularly stress, depression, and anxiety management, is critical for effective CVD rehabilitation. Interventions focused on stress management hold promise for reducing these negative psychological impacts, thereby enhancing patient health and recovery Objective: T o determine the early impact of successful primary percutaneous coronary intervention (PPCI) on left ventricular ejection fraction (LVEF) and clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI). Methods: This study included 60 STEMI patients who underwent PPCI from July 2023 to July 2024. Patients were included if presented within 6 hours of onset of symptom. LVEF was assessed at presentation and six months post-PPCI. The post-procedural TIMI flow grade was recorded. Data on patient demographics, comorbidities, and procedural outcomes were collected. Results: The mean age was 59.57 ± 10.46 years, with 71.7% male. LVEF at presentation was 36.70 ± 4.76%, which significantly improved to 54.88 ± 2.73% at six months (p = 0.0001). Post-PPCI, 66.7% of patients achieved TIMI grade 3 flow, and 33.3% had TIMI grade 2 flow. In-hospital mortality was 3.3%, and major adverse cardiac events (MACE) occurred in 5% of patients. Conclusion: Early successful PPCI in STEMI patients results in significant improvement in LVEF and favorable clinical outcomes.